2017
DOI: 10.15332/s1794-9998.2017.0001.09
|View full text |Cite
|
Sign up to set email alerts
|

Cooperación en Latinoamerica: red científica de psicología

Abstract: ResumenEste estudio investigó algunos aspectos de una red cooperativa dirigida a la Psicología Latinoamericana. El estudio se basó en datos documentales disponibles para el público. La red incluyó 262 investigadores latinoamericanos y 38 de otros países, puesto que la red apoya investigadores de otros continentes interesados en cooperar. Los datos investigados fueron el país de origen, el nivel educativo, la ocupación profesional, los intereses generales en cooperar y las modalidades de cooperación buscadas. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…Kliegl and Bates (2011) indicate that the levels of collaboration in the top psychology journals reached their peak in the 1990s. Although the present observation window begun in the 2000s, there is a similar increasing trend in collabo-ration, which has been pointed out in other studies and is supported by the cooperation and previous reports on psychology journals in Colombia (Ávila-Toscano, Marenco-Escuderos, & Madariaga Orozco, 2013;Garcia et al, 2016Garcia et al, , 2017Guerrero & Jaraba, 2009;López-López, de Moya Anegón, Acevedo-Triana, Garcia, & Silva, 2015). Although the data are not presented in this study, this collaboration has been found to be going through a change, moving from intra-institutional to national and international collaborations; as such, this category is necessary for the optimization of various kinds of resources.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Kliegl and Bates (2011) indicate that the levels of collaboration in the top psychology journals reached their peak in the 1990s. Although the present observation window begun in the 2000s, there is a similar increasing trend in collabo-ration, which has been pointed out in other studies and is supported by the cooperation and previous reports on psychology journals in Colombia (Ávila-Toscano, Marenco-Escuderos, & Madariaga Orozco, 2013;Garcia et al, 2016Garcia et al, , 2017Guerrero & Jaraba, 2009;López-López, de Moya Anegón, Acevedo-Triana, Garcia, & Silva, 2015). Although the data are not presented in this study, this collaboration has been found to be going through a change, moving from intra-institutional to national and international collaborations; as such, this category is necessary for the optimization of various kinds of resources.…”
Section: Discussionsupporting
confidence: 91%
“…In turn, technological developments require the integration of multiple sources. Accordingly, productivity analyses using a bibliometric approach allow areas of greater or lesser proximity to be identified, and, thus, the interdisciplinarity of knowledge (Heberger et al, 2010); furthermore, similar analyses have been conducted on cooperation between authors or types of research (Garcia, López-López, Acevedo-Triana, & Nogueira Pereira, 2017;Robayo-Castro, Rico, Hurtado-Parrado, & Ortega, 2016). This cooperation could be understood as joint efforts towards the common goal of scientific productivity (Garcia, López-López, Acevedo-Triana, & Bucher-Maluschke, 2016).…”
mentioning
confidence: 99%
“…Collaboration between Latin American institutions was only observed in one instance (Colombia-Mexico). Both of these findings are aligned with previously reported patterns of collaboration (i.e., typically with non-Latin American institutions), which have been explained by the need of better visibility, research quality, impact factors, or international recognition (García et al, 2017).…”
Section: Research On Emotion and Learning: Contributions From Latin Asupporting
confidence: 89%
“…Psychology in Latin America not only has a significant history as a discipline and profession, but also an important capacity for organization and response to exceptional phenomena such as the current one (Ardila, 1986;Gallegos, 2010Gallegos, , 2016aGarcía et al, 2017;Klappenbach et al, 2018;López-López et al, 2015;Saforcada, 2003). As psychologists and other health scientists began the novel task of examining the impact of the Covid-19 pandemic in the region, the number of studies has increased dramatically.…”
Section: Palavras-chavementioning
confidence: 99%